Mycophenolate Mofetil for the Treatment of Autoimmune Hepatitis in Patients Refractory or Intolerant to Conventional Therapy - Kaveh Sharzehi; Mary Ann Huang; Ian R Schreibman; Kimberly A Brown (Canadian Journal of Gastroenterology)
BACKGROUND: Autoimmune hepatitis is characterized by hepatocellular inflammation often progressing to cirrhosis. Standard treatment consists of corticosteroids and azathioprine. For the 20% of patients with refractory disease or those who are intolerant to medication, there is no standardized treatment.